2016
DOI: 10.1007/s11999-015-4438-z
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Femoral Neck Failure after THA with the Accolade® I Stem in Three Patients

Abstract: Case Description We report a series of three femoral stem failures, each occurring at the head-neck junction, with all patients experiencing limited and painful ambulation, leading to subsequent revision arthroplasty. All patients were male with high-offset femoral stems and increased head lengths, and each had undergone primary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…A further contributing factor is the accelerated corrosion of TMZF in simulated body fluid in comparison to Ti6Al4V, which might further precipitate the process [30]. It is surprising that the catastrophic GTF cases did apparently not exhibit clinical symptoms due to raised Co and Cr metal ions, which must have been caused by the amount of CoCr lost from the female head taper (above 15mm³, Figure 6, Figure 7), and/or the large amounts of taper, even so the extend is much larger [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further contributing factor is the accelerated corrosion of TMZF in simulated body fluid in comparison to Ti6Al4V, which might further precipitate the process [30]. It is surprising that the catastrophic GTF cases did apparently not exhibit clinical symptoms due to raised Co and Cr metal ions, which must have been caused by the amount of CoCr lost from the female head taper (above 15mm³, Figure 6, Figure 7), and/or the large amounts of taper, even so the extend is much larger [9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on elevated metal ion levels or even catastrophic gross taper failures (GTF) after hip joint replacement highlight one particular stem design with a small V-40 taper made from a less stiff Ti-12Mo-6Zr-2Fe titanium-alloy (TMZF; Accolade I, Stryker, Mahwah, NJ) in combination with head sizes of mostly 36mm and above ( Figure 1) [9][10][11][12][13][14][15][16][17][18]. This proprietary beta titanium alloy was introduced in 2002 based on the potential benefits of more closely mimicking the modulus of elasticity of cortical bone than standard Ti-6Al-4V alloys [19].…”
Section: Introductionmentioning
confidence: 99%
“…Head-neck taper corrosion was not listed as a potential mode of failure as part of the recall. These two types of failure have been observed across a range of other manufacturers as a rare event[610, 19–22]. …”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported ALTR association with head-neck taper corrosion[6, 7] and with gross trunnion failure (GTF)[8]. A small series of cases involving GTF with the Low Friction Ion Treatment (LFIT) CoCr femoral head and the Accolade titanium-molybdenum-zirconium-iron alloy (TMZF) stem, as well as other designs, has also been reported[9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Fracture of the femoral component of a total hip arthroplasty is a rare cause for revision compared with infection, aseptic loosening, and instability [1] , [2] . Fracture of both cemented and cementless femoral component stems has been reported [1] , [2] , [3] , [4] . In the 1970s, the reported rate of stem fracture ranged from 0.23% to 10.7% [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%